"One-drop-of-blood" electroanalysis of lead levels in blood using a foam-like mesoporous polymer of melamine–formaldehyde and disposable screen-printed electrodes1. Issue 6 (21st March 2015) - Zhao, Yanfang; Xu, Lubin; Li, Shuying; Chen, Qi; Yang, Daoshan; Chen, Lingxin; Wang, Hua
<x xml:space="preserve">Abstract</x> A foam-like mesoporous melamine–formaldehyde polymer was synthesized and deposited on disposable screen-printed electrodes for the electroanalysis of Pb2+ ions in blood.